Peranan Kegiatan Kuliah Kerja Nyata (KKN) UPNVYK Dalam Media Literasi Digital Pada Masyarakat Pedesaan - Awang Hendrianto Pratomo (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
Increasing digital literacy is crucial in the age of digital transformation, especially in rural communities. Data from the Ministry of Communication and Informatics (KOMINFO) shows that Indonesia's Digital Literacy Index has seen improvement, but challenges persist, particularly in marginalized rural areas. To address this, the 77th batch of Kuliah Kerja Nyata (KKN) at UPN